A Flow-Cytometric Analysis of Spectrum of Acute Myeloid Leukemia at Diagnosis - Shetty, Parineetha V; I, Sandhya; Anand, Ishant; G, Prithal; Rao, Purnima; Shetty, Rachan (Annals of Pathology and Laboratory Medicine, 2021)
Background: Acute Myeloid Lymphoma is the clonal proliferation of non-lymphoid blasts comprising at least 20% of total nucleated cells either in bone marrow or peripheral blood. In the recent years, flow cytometry has emerged as a powerful diagnostic tool for AML due to its impact on treatment and prognosis. Aims & Objectives: To analyse the flow cytometry findings in patients diagnosed as acute myeloid leukemias. To evaluate variations in flow cytometry expression in various subtypes of acute myeloid leukemia Materials & Methods: Patients diagnosed as acute myeloid leukaemia on peripheral smears were subjected to flow cytometry analysis. This was a four-year study from July 2015 to June 2017 retrospectively and from July 2017 to June 2019 prospectively. Results: A total of 27 cases diagnosed as Acute Myeloid Leukemia (AML) were included in the study. Acute Promyelocytic Leukemia was observed to be the most common subtype. The most commonly expressed myeloid antigens were CD13 and CD33. There was an aberrant expression of CD7 and CD56 in 1 case each indicating adverse prognosis. Conclusion: Immunophenotyping of the myeloid cells by flow cytometry has revolutionised the diagnosis of acute myeloid leukemias. It aids in confirming the morphological diagnosis, and also helps in assigning specific lineage, accurate sub classification and adequate treatment in challenging cases. Aberrant expressions were observed in 3 cases of AML. Aberrant antigen expression is associated with a poor outcome. Flow cytometry results interpreted with morphology are not only complementary but also conclusive aiding in therapeutics and predicting prognosis.